A Newly Designed Infrared Reflection Absorption Spectroscopy System for In Situ Characterization from Ultrahigh Vacuum to Ambient Pressure. Issue 1 (January 2018) - Du, Yunshu; Li, Ling; Wang, Xuan; Qiu, Hengshan
We present a novel ultrahigh vacuum (UHV) compatible polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) system that is designed for in situ surface spectroscopic characterization on a transferable single crystalline sample. The innovative design of manipulator rod and high-pressure cell (HPC) ensures free movement of the sample between the preparation chamber and the HPC, and perfect separation of them during high pressure experiments. The pressure in the HPC can be varied from UHV (10 −9 mbar) to ambient pressure (1000 mbar) while keeping the preparation chamber under UHV conditions. The design of the transferable sample holder and receiving stage allows precise temperature measurement and allows convenient sample changing. In situ IRRAS measurements under variable pressure and temperature can be conducted either in the conventional mode or with polarization modulation. Other surface characterization methods can also use the preparation chamber; thus, the system is endowed with the capability for systematic investigations of surface catalytic reactions. A case study of CO adsorption and oxidation on Pt(111) demonstrates the performance of the system.